Intraindividual variability across cognitive tasks as a potential marker for prodromal Alzheimer’s disease - Kälin, Andrea M.; Pflüger, Marlon; Gietl, Anton F.; Riese, Florian; Jäncke, Lutz; Nitsch, Roger M.; Hock, Christoph (Frontiers in Aging Neuroscience, 2014)
Recent studies have shown that increased cognitive intraindividual variability (IIV) across accuracy scores from tests representing different cognitive domains (across-domain IIV) might indicate prodromal Alzheimer’s disease (AD). Although IIV has been proposed to index cognitive control processes, IIV across accuracy scores from cognitive control tasks (within-domain IIV) has not been examined in healthy controls subjects (HCS), mild cognitive impairment (MCI) and AD patients in a single comparative study. This study examines the discriminative properties of within-domain IIV, and across-domain IIV in 149 HCS, 31 MCI and 26 AD. Three tasks representing different cognitive domains were identified to calculate across-domain IIV. Three other tasks representing cognitive control were identified to calculate within-domain IIV. The intraindividual standard deviation (ISD) was calculated across accuracy scores. To compare IIV between groups, ANCOVAs with the covariates age, gender, education, and mean performance were computed. IIV scores in general were higher in AD vs. HCS (p< 0.01). Only across-domain IIV was higher in AD vs. MCI (p=0.001), and only within-domain IIV was higher in MCI vs. HCS (p=0.05). Within-domain IIV may constitute a cognitive marker for the detection of prodromal AD at the MCI stage, whereas across-domain IIV may detect beginning AD at the MCI stage.